PENGARUH PENGGUNAAN SMARTPHONE TERHADAP KUALITAS BELAJAR SMAN 1 BUKITTINGGI - M.Kevin Yosiva Arza (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
This study aims to look at the effect of the use of smartphones on the quality of student learning in SMA N 1 Bukittinggi. This type of research is quantitative research with a correlational approach. The population of this research is 69 students of SMA N 1 Bukittinggi who have studied using a smartphone in the January-March semester. Sampling uses a random sampling technique using the Slavin method, so that there are 50 respondents for research and 20 respondents for testing instruments. The instrument in this study used a closed questionnaire with a Likert scale. Data were analyzed with the help of SPSS version 22. The results showed that there was a relationship between the use of smartphones to the quality of student learning in SMA N 1 Bukittinggi with a correlation coefficient of 0.2787. This value means having a high relationship. Furthermore, regression analysis is performed to see the effect between the use of E-Learning learning media on student learning motivation and get a regression coefficient (x) of 0.816. This value means that every 1% increase in the value of the use of a smartphone to the positive learning quality variable is positive.